2008
DOI: 10.1021/ja805356j
|View full text |Cite
|
Sign up to set email alerts
|

Diene Hydroacylation from the Alcohol or Aldehyde Oxidation Level via Ruthenium-Catalyzed C−C Bond-Forming Transfer Hydrogenation: Synthesis of β,γ-Unsaturated Ketones

Abstract: Under the conditions of ruthenium catalyzed transfer hydrogenation, isoprene couples to benzylic and aliphatic alcohols 1a–1g to deliver β,γ-unsaturated ketones 3a–3g in good to excellent isolated yields. Under identical conditions, aldehydes 2a–2g couple to isoprene to provide an identical set of β,γ-unsaturated ketones 3a–3g in good to excellent isolated yields. As demonstrated by the coupling of butadiene, myrcene and 1,2-dimethylbutadiene to representative alcohols 1b, 1c and 1e, diverse acyclic dienes par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(86 citation statements)
references
References 32 publications
0
86
0
Order By: Relevance
“…This result demonstrated that the hydrogen and acyl units that add to the diene do come from different molecules of aldehydes. 13 In summary, we have developed an efficient cross-addition reaction catalyzed by RuHCl(CO)(PPh 3 ) 3 , which provides entry to a wide variety of ,γ-unsaturated ketones starting from the corresponding aldehydes and dienes. The detailed mechanism of this reaction as well as further extension of this chemistry is currently under investigation in this laboratory.…”
mentioning
confidence: 99%
“…This result demonstrated that the hydrogen and acyl units that add to the diene do come from different molecules of aldehydes. 13 In summary, we have developed an efficient cross-addition reaction catalyzed by RuHCl(CO)(PPh 3 ) 3 , which provides entry to a wide variety of ,γ-unsaturated ketones starting from the corresponding aldehydes and dienes. The detailed mechanism of this reaction as well as further extension of this chemistry is currently under investigation in this laboratory.…”
mentioning
confidence: 99%
“…Ru-catalyzed hydroacylation of 2a generates C3-selective products [3,4]. The proposed mechanism includes hydrometalation of 1,3-diene, carbonyl addition and beta-H elimination steps.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ruthenium catalyst (F 3 CCO 2 )(H)Ru(CO)(PPh 3 ) 2 , which is generated in situ through the acid base reaction of H 2 Ru(CO)(PPh 3 ) 3 and F 3 CCO 2 H, possesses a higher degree of coordinative unsaturation, enabling β-hydride elimination at the stage of the homoallylic ruthenium alkoxide to form the β,γ-unsaturated enones (Scheme 2). 32 Notably, both transformations, diene hydrohydroxyalkylation or hydroacylation, may be conducted from the alcohol or aldehyde (not shown) oxidation level of the reactant. 31,32 Initial studies aimed at directing relative and absolute stereochemistry in alcohol mediated diene hydrohydroxyalkylation relied on the use of 2-trialkylsilyl-butadienes.…”
Section: Conversion Of Primary Alcohols To Secondary Alcoholsmentioning
confidence: 99%
“…32 Notably, both transformations, diene hydrohydroxyalkylation or hydroacylation, may be conducted from the alcohol or aldehyde (not shown) oxidation level of the reactant. 31,32 Initial studies aimed at directing relative and absolute stereochemistry in alcohol mediated diene hydrohydroxyalkylation relied on the use of 2-trialkylsilyl-butadienes. 33 Hydrometalation of 2-trialkylsilyl-substituted dienes gives rise to crotylmetal species that exist as single geometrical isomers due to allylic strain.…”
Section: Conversion Of Primary Alcohols To Secondary Alcoholsmentioning
confidence: 99%